The idea of political marketing - O'Shaughnessy, Nicholas J., 1954-; Henneberg, Stephan C. M. (Praeger series in political communication., 2002)
O'Shaughnessy, Henneberg, and their contributors examine how the theory and practice of marketing has been and can be applied to politics. Particular attention was paid to the theory of political marketing, with conceptual definitions developed to better facilitate communication between marketing professionals and political science researchers.